Assembling Sn3O4 nanostructures on a hydrophobic PVDF film through metal-F coordination to construct a piezotronic effect-enhanced Sn3O4/PVDF hybrid photocatalyst. (June 2020) - Han, Shuwei; Chen, Duo; Wang, Jian; Liu, Zhen; Liu, Fan; Chen, Yuke; Ji, Yanchen; Pang, Jinbo; Liu, Hong; Wang, Jingang
Abstract: Piezotronic effect has been thought as a general approach for building high performance hybrid photocatalysts by integrating semiconductor nanostructures on piezoelectric materials. Although polyvinylidene fluoride (PVDF) has been widely applied as a flexible piezoelectric material, it is thought that assembling inorganic semiconductor nanostructures on PVDF surface is promising owing to the high hydrophobic property of PVDF. In this study, we proposed that the coordination effect between a metal ion and an exposed fluorine atom on the surface of PVDF can be used to assemble a layer of photocatalytic metal oxide nanostructures on the PVDF film surface. Using Sn3 O4 as a model oxide, a Sn3 O4 /PVDF hybrid nanostructured photocatalyst was successfully synthesized. The X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy results confirmed the existence of coordinated bonds between F ions and metal ions, which could explain the stable growth of inorganic nanostructures on the hydrophobic surface of PVDF. At the interface between Sn3 O4 and PVDF in the hybrid nanostructured photocatalyst, a built-in electric field was constructed on the basis of the ferroelectric field of the PVDF film, which induced an enhanced photocatalytic property. Most importantly, the swing driven by flowing water can considerably enhance photocatalytic properties owing to the piezotronic effect-driven alternating reconstruction of built-in electric field induced by the deformation of PVDF film. This study provides an approach for the synthesis of metal oxide semiconductor nanostructures on hydrophobic PVDF polymer surface. The developed material will have many applications in the photodegradation of organic pollutants in waste water. Graphical abstract: Image 1 Highlights: Assembled Sn3 O4 nanostructures on a hydrophobic PVDF film through metal-F coordination. The spontaneous electric potential of PVDF acts as a built-in electric field of Sn3 O4 /PVDF. Piezotronic effect enhances the activity of Sn3 O4 /PVDF photocatalyst just driven by water flow.